2020
DOI: 10.1029/2019jf005397
|View full text |Cite
|
Sign up to set email alerts
|

Morphodynamic Evolution of a Fringing Sandy Shoal: From Tidal Levees to Sea Level Rise

Abstract: Intertidal shoals are vital components of estuaries. Tides, waves, and sediment supply shape the profile of estuarine shoals. Ensuring their sustainability requires an understanding of how such systems will react to sea level rise (SLR). In contrast to mudflats, sandy shoals have drawn limited attention in research. Inspired by a channel-shoal system in the Western Scheldt Estuary (Netherlands), this research investigates governing processes of the long-term morphodynamic evolution of intertidal estuarine sand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 67 publications
(110 reference statements)
1
20
0
Order By: Relevance
“…DeVet et al (2018) showed that a sandy shoal may propagate along the wave direction and wind direction. Elmilady et al (2020) highlight that wave-induced resuspension is essential for distributing sediment supplied from deep channels over the intertidal flat.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…DeVet et al (2018) showed that a sandy shoal may propagate along the wave direction and wind direction. Elmilady et al (2020) highlight that wave-induced resuspension is essential for distributing sediment supplied from deep channels over the intertidal flat.…”
Section: Introductionmentioning
confidence: 93%
“…Arafat et al, 2016;Dam et al, 2016;Elmilady et al, 2019;Ganju & Schoellhamer, 2010;Luan et al, 2017). Other studies have focused on exploring morphodynamics of isolated tidal flats by using one-dimensional (1D) profile models (e.g., Maan et al, 2015;Zhou et al, 2015) or twodimensional (2D) models (e.g., DeVet et al, 2018;Elmilady et al, 2020;Fagherazzi et al, 2007;Nguyen et al, 2011). These studies apply a numerical process-based model to study estuarine morphodynamic development and show its increasing potential and reliability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations